Expressão numérica: a hierarquia das quatro operações matemáticas - Ottes, Aline Brum (2016)
For the development of this work, in the introduction we present a few topics which motivated it, as well as the research problem and its reason. The main objective of this dissertation is to research on the possible reasons for the hierarchy of the four mathematical operations. With this purpose, we attempted to verify if there were some explanations for such hierarchy. Thus, we researched on national and international sites. On this search, we found two articles of interest, namely: “the order of operation in elementary arithmetic” and the thesis “the school mathematics knowledge: operations with the natural numbers in the grade and middle school”, which were formulated comments about them. This research is classified as qualitative and bibliographical descriptive. In the chapter about the theory we presented how the subject numerical expression is explained in some official documents, as well as in textbooks of the Middle School. Since we have not found any reasonable and plausible explanation for such hierarchy, we included a chapter about a historical retrospective on the order of operations and the use of the parenthesis which, in turn, prepared the way for the chapter on a proposal to justify the why of the hierarchy for the four mathematical operations.